The struggle within dual systems of government: dealing with conflict between traditional leaders and ward councilors in the greater Giyani Municipality in South Africa - Muchaku, Shadreck; Magaiza, Grey (Frontiers in Political Science, 2024)
Current frameworks of conflict resolution have experienced partial success. Several conflicts experienced in local Municipalities reflect the need for context-specific frameworks that backstop leadership conflicts while building peace. Given the conspicuous lack of progress on how these conflicts can be resolved, we attempt to provide useful insights on how this drawback can be addressed by identifying the major challenges that continue to undermine our abilities to assimilate and implement objectively informed conflict resolution strategies that are premised on qualitative investigation strategies. A purposive sampling method was used to select 33 respondents from the Greater Giyani Municipality. Data were collected using semi-structured interview guidelines and analysed through statistically established matrix scoring procedures of responses that were solicited from key informants and group discussions. ATLAS.ti 8 software techniques (code primary document tables and networks) were employed to analyse data. Although this paper does not provide an exhaustive analysis of the challenges that threaten the co-existence of the dual system of government in local communities in South Africa, it does highlight certain examples of externalities that require attention, such as leadership conflicts and unsustainable peace. The reasons for the escalation and resurgence of conflict include capacity limitations, lack of inclusivity, bias, divisive decision-making and contentious court rulings. With our limited ability to identify where, when and how these conflicts can be amicably resolved, the scientific community must provide the critical but hard-to-find information needed to respond effectively to these challenges.